Artikulasi Jersey Persib 2014 - Sri Soedewi (Pascasarjana ISBI Bandung, 2019)
Persib jersey 2014 is the pride for bobotoh, because Persib became a champion for Indonesia Super League (ISL) competition in 2014. Not only to a! ract the customer, good performance of Persib also to attract the sponsor to promote their brands. Local culture of West Java use for Persib jersey 2014 design elements and become an interesting phenomenon in the middle of the issue of local culture decrease. Production of Persib jersey 2014 trough some processes, like simplifi cation to icon, logo, and design elements in jersey. Artwork design created from internal and external infl uences. The internal infl uences are idea/concept, regulation of FIFA, PSSI, and media requirements. The External infl uence is to understand the audience taste/trend. There are some processes such as regulation, signifi cation, consumption, production, and identity relates each others. In order to understand the meaning of Persi jersey of 2014, the Circuit of culture was created to fi nd the interrelated from as many angles, and in as many contexts, as possible to articulating the meaning. From the relation between Circuit of culture moments in Persib jersey, the meaning is spirit of team togetherness to victory until they become the pride of West Java.Keywords: Persib jersey, local culture, articulation, circuit of culture, the pride